Configuring Epistemic Authority: The Significance of Film Style in Documentaries about Science. Issue 1 (27th March 2018) - Mellor, Felicity
Argument: Among the many limitations of the deficit model of science communication is its inability to account for the qualities of communication products that arise from creative decisions about form and style. This paper examines two documentaries about the nature of time – Patricio Guzmán's Nostalgia for the Light and the first episode of the BBC's Wonders of the Universe series – in order to consider how film style inflects science with different meanings. The analysis pays particular attention to the ways in which authority is assigned between film author, narrator, and depicted subjects and the degree to which different film styles promote epistemological certainty or hesitancy.